Pengaruh Pemanfaatan Film Pendek Melalui Layanan Informasi terhadap Peningkatan Perilaku Disiplin Siswa di SMP Negeri 22 Kota Jambi - Siti Amanah; Andre Kurniawan; Akmal Sutja (Departement of Mathematics Education, 2023)
Learning discipline is a series of attitudes, student behavior that shows obedience and obedience to study regularly both at school and at home. But in reality in schools there are still many students who do not achieve optimal development, one of which needs to be considered is that there are still many student behaviors that are not disciplined in learning. This study aims to determine the effect of using short films through information services on improving student learning discipline. This type of research is a true experimental study with a pre-test and post-test design conducted at SMPN 22 Jambi City. The population of this study was class VIII with the sample in this study as many as 2 classes, namely class VIII B which amounted to 30 students and class VIII C totaled 28 students. The results showed that the students learning discipline in the experimental group and the control group had a difference in the average value of the experimental group's learning discipline with an average value of 104.367 in the HIGH category and in the control group an average value of 94.857 was obtained in the HIGH category. On the output test results of the independent sample t-test using SPSS version 26.0, the Tcount value is 3.124. The Ttable value is 0.05, which is 2.003. It can be seen that the value of TCount > Ttable or 3.124 > 2.003. Sig (2-tailed) 0.000 < 0.05. It can be seen that there is a significant difference between the results of increasing the learning discipline of students in the experimental group and the control group. When analyzed from the basis of decision making or acceptance criteria, H0 is rejected and Ha is accepted. So it can be concluded that there is a significant influence on the use of short films through information services on improving student learning discipline behavior.